Stages Application of National Standards Research For Higher Universities - Fatimatul Zahra (CV. ADIBA AISHA AMIRA, 2022)
The need for minimum criteria regarding the research system at universities that apply in all jurisdictions of the Unitary State of the Republic of Indonesia. The national standard of research for lecturers is one of the activities of the Tri Dharma of Higher Education. These activities must be planned, implemented, monitored, and documented by the UPPM. National research standards consist of: 1. Research results standards 2. Research content standards 3. Research process standards 4. Research assessment standards 5. Research standards 6. Research facilities and infrastructure standards 7. Research management standards 8. Research funding and financing standards